Medical nutrition therapy in obesity management - Conradie-Smit, M; Fourie, V R; May, W (South African medical journal, 2025)
RECOMMENDATIONS We suggest that nutrition recommendations for adults of all body sizes should be personalised to meet individual values, preferences and treatment goals to support a dietary approach that is safe, effective, nutritionally adequate, culturally acceptable and affordable for long-term adherence (Level 4, Grade D). PLWO should receive individualised MNT provided by a registered dietitian (when available) to improve weight outcomes (body weight, BMI), waist circumference (WC) and glycaemic control, and to establish lipid and blood pressure (BP) targets (Level 1a, Grade A). PLWO and impaired glucose tolerance (prediabetes) or type 2 diabetes (T2DM) may receive MNT provided by a registered dietitian (when available) to reduce body weight and WC and improve glycaemic control and BP (Level 2a, Grade B). PLWO can consider any of the many medical nutrition therapies to improve health-related outcomes, choosing the dietary patterns and food-based approaches that support their best long-term adherence: CR dietary patterns emphasising variable macronutrient distribution ranges (lower, moderate or higher carbohydrate with variable proportions of protein and fat) to achieve similar body weight reduction over 6 - 12 months within a CR plan (Level 2a, Grade B). Mediterranean dietary pattern to improve glycaemic control, high-density lipoprotein cholesterol (HDL-C) and triglycerides (Level 2b, Grade C), reduce cardiovascular events (Level 2b, Grade C), reduce risk of T2DM (Level 2b, Grade C) and increase reversion of metabolic syndrome (Level 2b, Grade C),[11] with little effect on body weight and WC (Level 2b, Grade C) Vegetarian dietary pattern to improve glycaemic control and established blood lipid targets, including low-density lipoprotein cholesterol (LDL-C), and reduce body weight (Level 2a, Grade B), risk of T2DM (Level 3, Grade C), and coronary heart disease incidence and mortality (Level 3, Grade C). Portfolio dietary pattern to improve established blood lipid targets, including LDL-C, apolipoprotein B (apo B) and non-HDL-C (Level 1a, Grade B),[16] and reduce C-reactive protein (CRP), BP and estimated 10-year coronary heart disease risk (Level 2a, Grade B) Low glycaemic index dietary pattern to reduce body weight (Level 2a, Grade B), improve glycaemic control (Level 2a, Grade B) and established blood lipid targets, including LDL-C (Level 2a, Grade B), and reduce BP (Level 2a, Grade B)[20] and the risk of T2DM (Level 3, Grade C) and coronary heart disease (Level 3, Grade C). Dietary Approaches to Stop Hypertension (DASH) dietary pattern to reduce body weight and WC (Level 1a, Grade B), improve BP (Level 2a, Grade B), established lipid targets, including LDL-C (Level 2a, Grade B), CRP (Level 2b, Grade B)and glycaemic control (Level 2a, Grade B), and reduce the risk of T2DM, cardiovascular disease, coronary heart disease and stroke (Level 3, Grade C). Nordic dietary pattern to reduce body weight (Level 2a, Grade B)[26] and body weight regain (Level 2b, Grade B), improve BP (Level 2b, Grade B)[27] and established blood lipid targets, including LDL-C, apo B (Level 2a, Grade B)[28] and non-HDL-C (Level 2a, Grade B), and reduce the risk of cardiovascular and all-cause mortality (Level 3, Grade C) Partial meal replacements (replacing one to two meals per day as part of a CR intervention) to reduce body weight, WC and BP and improve glycaemic control (Level 1a, Grade B). Intermittent and continuous CR achieved similar short-term body weight reduction (Level 2a, Grade B) Pulses (i.e. beans, peas, chickpeas, lentils) to improve body weight (Level 2, Grade B), glycaemic control (Level 2, Grade B), established lipid targets, including LDL-C (Level 2, Grade B), and systolic BP (Level 2, Grade C), and reduce the risk of coronary heart disease (Level 3, Grade C). Vegetables and fruit to improve diastolic BP (Level 2, Grade B) and glycaemic control (Level 2, Grade B),[39] and reduce the risk of T2DM (Level 3, Grade C) and cardiovascular mortality (Level 3, Grade C). Nuts to improve glycaemic control (Level 2, Grade B) and established lipid targets, including LDL-C (Level 3, Grade C) and reduce the risk of cardiovascular disease (Level 3, Grade C). Whole grains (especially from oats and barley) to improve established lipid targets, including total cholesterol and LDL-C (Level 2, Grade B). Dairy foods to reduce body weight, WC and body fat and increase lean mass in CR diets, but not in unrestricted diets (Level 3, Grade C), and reduce the risk of T2DM and cardiovascular disease (Level 3, Grade C). PLWO and impaired glucose tolerance (prediabetes) should consider intensive behavioural interventions that target a 5 - 7% weight loss to improve glycaemic control, BP and blood lipid targets (Level 1a, Grade A), reduce the incidence of T2DM (Level 1a, Grade A)[48] and microvascular complications (retinopathy, nephropathy and neuropathy) (Level 1a, Grade B), and reduce cardiovascular and all-cause mortality (Level 1a, Grade B). PLWO and T2DM should consider intensive behavioural therapy that targets a 7 - 15% weight loss to increase the remission of T2DM (Level 1a, Grade A) and reduce the incidence of nephropathy (Level 1a, Grade A) obstructive sleep apnoea (Level 1a, Grade A) and depression (Level 1a, Grade A) We recommend a non-restrictive dietary approach to improve QoL, psychological outcomes (general wellbeing, body image perceptions), cardiovascular outcomes, body weight, physical activity, cognitive restraint and eating behaviours (Level 3, Grade C).